Analysis of Government Residential Projects Overruns in Jordan - Albtoosh, Ja’far A. Aldibat; Ahmad Tarmizi, Haron; Shaqdan, Ashraf (Medwell Journals, 2018)
Construction sector is one of the major drivers in jordan economy to many sectors related directly or indirectly to construction sector. Construction projects require a range of services that provide jobs for a large fraction of population depends on. Recently, the construction industry economy is facing many challenges that caused slow down. Therefore, a deep analysis for the construction industry is needed. This research focuses on the understanding of Over Run (OR) situation in building projects in Jordan. It is designed broadly in two parts. Part one aimed at establishing critical issues of OR and their causes in building projects in Jordan. This part involved four stages; problem definition, literature review, case study. From the analysis, we identified that overruns as major challenge that often cause additional cost burden on projects budgets.